Bond behaviors of BFRP bar-to-concrete interface under dynamic loading. (25th October 2021) - Chen, Wanxiang; Meng, Fanjun; Sun, Hang; Guo, Zhikun
Highlights: Bond behaviors of BFRP bar-to-concrete interface under dynamic loading are experimentally investigated. An improved bond stress-slip model of BFRP bar-to-concrete interface is proposed. The reliabilities of proposed model are validated by a series of pull-out tests. Abstract: Bond performances of BFRP bar embedded in concrete is a critical issue in the design of reinforced concrete structures under dynamic loadings. 16 groups of pull-out specimens are fabricated to investigate the dynamic bond behaviors of BFRP bar-to-concrete interface using MTS test system. The influences of loading rate, concrete strength and rebar diameter on bond performances are analyzed. Bond strengths of BFRP bar-to-concrete interface under displacement rates varying between 0.005 mm/s and 5 mm/s are estimated and an improved bond stress-slip model is further developed. Results indicate that the specimens are failed mainly due to the pull-out of BFRP bar and the split of concrete. The bond strengths increase with the concrete strengths and the loading rates, but decrease significantly with the diameter of BFRP bar. The analytical curves are in good agreement with the experimental results, demonstrating that it could be employed to reasonably describe the bond behaviors of BFRP bar embedded in concrete under dynamic loadings.